2012
DOI: 10.1094/cm-2012-0925-02-rs
|View full text |Cite
|
Sign up to set email alerts
|

Cattle Grazing Affects Cotton Root Dimensions and Yield in a Bahiagrass-based Crop Rotation

Abstract: With increasing production costs in the southeastern US, cropping systems that improve agronomic and economic sustainability are critical. A sod‐based system utilizing a two year rotation of establishing and grazing bahiagrass (Paspalum notatum Flueggé) followed by a year of peanut (Arachis hypogaea L.) and a year of cotton (Gossypium hirsutum L.) was established in Marianna, FL. The effect of grazing in this system on root dimensions (length, diameter, and surface area) of cotton was monitored using a mini‐rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…However, in the nongrazed plots such differences in the root parameters at different depths were not observed (Table 3). As previously noted in cotton by Loison et al (2012) grazing did not negatively impact root traits in the top soil due to soil compaction. In a related study on peanut in 2009, a slight increase in bulk density was observed at 0-5 cm in the grazed plots as compared to the non-grazed plots.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…However, in the nongrazed plots such differences in the root parameters at different depths were not observed (Table 3). As previously noted in cotton by Loison et al (2012) grazing did not negatively impact root traits in the top soil due to soil compaction. In a related study on peanut in 2009, a slight increase in bulk density was observed at 0-5 cm in the grazed plots as compared to the non-grazed plots.…”
Section: Resultssupporting
confidence: 82%
“…Peanut grown in the sod-based rotation system with cattle grazing has shown higher yields with reduced costs (Marois et al, 2002). Grazing in a sod-based rotation system has also shown increased root development (Loison et al, 2012), enhanced microbial and enzyme activity and nutrient recycling (Anguelov et al, 2011;Vendramini et al, 2007;Wright et al, 2010;George et al, 2013).…”
mentioning
confidence: 99%
“…The high lint yields attained with the moderate N rates may be attributed to cattle grazing. Grazing winter crops has shown to increase peanut and cotton yields with increased root development in terms of root length, surface and root volume (Loison et al, 2012; Marois et al., 2002; Sidhu et al., 2018) along with enhanced microbial and enzyme activity and nutrient recycling (Anguelov et al., 2011; George et al., 2013; D. L. Wright et al, unpublished data, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A study in Brazil found high grazing intensity reduced soil water content relative to low‐to‐moderate grazing intensities, which was attributed to increased porosity and root growth without compacting the soil with light‐to‐moderate grazing compared with high‐intensity grazing (Bonetti et al., 2019). A study in Florida reported that increased cotton root biomass and soil organic matter with grazing CCs was probably responsible for greater soil water content at the 30‐ and 100‐cm depth in grazed compared with non‐grazed CCs (Loison et al., 2012). Thus, in a few cases, the potential enhancement in soil C and related soil properties under CC grazing could lead to increased soil water content relative to fields without CCs and grazing.…”
Section: Impacts Of Grazing Cover Crop On Soil Propertiesmentioning
confidence: 99%